1998
DOI: 10.1136/hrt.80.6.596
|View full text |Cite
|
Sign up to set email alerts
|

Increased orthostatic tolerance following moderate exercise training in patients with unexplained syncope

Abstract: Objective-To determine whether a programme of simple, moderate exercise training increases blood volume and improves orthostatic tolerance in patients with attacks of syncope or near syncope related to orthostatic stress.Design-An open study in 14 patients referred with unexplained attacks of syncope, who were shown to have a low tolerance to an orthostatic stress test. Measurements were made of plasma and blood volumes, orthostatic tolerance to a test of combined head up tilt and lower body suction, and baror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…increased dietary salt/electrolyte intake with fluids such as 'sport' drinks, salt tablets) or moderate exercise training [269][270][271][272] appear to be among the safest initial approaches (level B). Additionally, in highly motivated patients with recurrent vasovagal symptoms, the prescription of progressively prolonged periods of enforced upright posture (so-called 'tilt-training') may reduce syncope recurrence [273,274] (level B).…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…increased dietary salt/electrolyte intake with fluids such as 'sport' drinks, salt tablets) or moderate exercise training [269][270][271][272] appear to be among the safest initial approaches (level B). Additionally, in highly motivated patients with recurrent vasovagal symptoms, the prescription of progressively prolonged periods of enforced upright posture (so-called 'tilt-training') may reduce syncope recurrence [273,274] (level B).…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…This is presumably because, with a larger blood volume, more is available for filling the dependent capacitance vessels. It has also been shown that orthostatic tolerance improves if blood volume can be increased, for example by salt loading [4,5] or by exercise training [6].…”
mentioning
confidence: 99%
“…18 It is said that postural changes, such as standing up, elicit sympathetic stimulation which, if attenuated, may be a marker of early sympathetic impairment. 44 However, it may also be an indication of exercise induced changes in the ANS. It is important to take cognisance of the fact that the orthostatic response can detect effects not visible in the supine position and that it can be a useful clinical tool to measure autonomic responsiveness, both in clinical medicine 45 and in exercise physiology.…”
mentioning
confidence: 99%